Authentic Assessment in Islamic Education: Challenges and Practice - Julhadi Julhadi; Metriadi Metriadi; Hendra Sasputra; muhammad syarif; Adhitya Adhitya (Ahlussunnah: Journal of Islamic Education, 2026)
Assessment practices in Islamic Education have predominantly relied on written tests that emphasize cognitive outcomes, often neglecting students’ attitudes and skills. This study aims to examine the implementation of authentic assessment as a comprehensive evaluation approach by integrating theoretical perspectives and practical realities. Using a qualitative method with a content analysis approach, this study synthesizes contemporary assessment theories and relevant empirical findings. The results indicate that authentic assessment methods, such as performance tasks, projects, and portfolios, are theoretically appropriate for measuring the internalization of Islamic values and students’ real-life behavior. However, their implementation faces significant challenges, particularly related to administrative complexity and limited instructional time. This study highlights the need for more practical assessment designs and the enhancement of teachers’ competencies in developing objective assessment rubrics to support effective character education.